Respuesta :

Answer: -2a² + 2a + 2

Step-by-step explanation:

Given worded expression

subtract the sum of  (8a-6a²+9) and (-10a-8+8a²) from 3

Convert to numerical expression

3 - [(8a - 6a² + 9) + (-10a - 8 + 8a²)]

Expand parentheses in the bracket

=3 - [8a - 6a² + 9 - 10a - 8 + 8a²]

Combine like terms in the bracket

=3 - [(-6a² + 8a²) + (8a - 10a) + (9 - 8)]

=3 - [2a² - 2a + 1]

Expand bracket

=3 - 2a² + 2a - 1

Combine like terms

=-2a² + 2a + (3 - 1)

=[tex]\boxed{-2a^2+2a+2}[/tex]

Hope this helps!! :)

Please let me know if you have any questions

ACCESS MORE